Geodiversity and geo-education in the construction of tourist and leisure territories: the case of Estrela Aspiring Geopark (AGE) - Fernandes, Magda (2020)
Geodiversity has an intrinsic enormous scientific value in allowing us to understand the evolution of our Planet. In this sense, it is necessary to implement strategies to preserve geodiversity, through geoconservation. In order to disseminate and promote geological heritage, some territories seek to develop educational programs that promote direct contact with geoheritage, contributing to the recognition of its importance and consequently of the need for its conservation. In implementing educational promotion strategies, with the use of properly prepared guides and appropriate educational materials, teachers are encouraged to promote field lessons at different levels of education, contributing to increasing the interest in geosciences, as well as for a better understanding of other phenomena occurring on Earth. With the objective of promoting the development of value-added activities, based on geodiversity, we have seen a tourist appropriation of these resources, giving rise to geotourism strategies. We are thus faced with a potential form of sustainable tourism that can contribute to the economic development of many regions, while respecting sustainability criteria. In the Aspiring Geopark Estrela the geoconservation of geological heritage takes place through the implementation of key methods, such as inventories of geosites, with evaluation of its scientific, educational, cultural and touristic value; the implementation of signage, exhibitions, and interpretative panels accessible to all and the establishment of interpretative routes. Will be presented some examples of the different educative programs that are being currently promoted and directed to the disciplinary areas of the Geosciences. Our approach allows an interdisciplinary with other areas of knowledge, such as, Biology, Geography, History and Archaeology.